An overview of human resource traning in colleges and universities in hospitality and tourism in Vietnam: The limitations and recommendations - Kiều, Tiên (Tạp chí Khoa học HUFLIT, 2022)
Tourism and hospitality industry is one of the largest and rapidly growing industries not only in Vietnam but also in the world. In Vietnam, it creates lots of jobs for different kinds of people and generates large amount of revenue. Whether the hospitality and tourism businesses succeed or not would mainly base on how customers feel about the service and the service value perceived. The need for outstanding service delivery, improved service quality, excellent customer satisfaction has led to better strategies in training human resource. The availability of well-trained employees plays an important role in the success of any tourism and hospitality businesses. However, there is a severe shortage of skilled manpower both in quality and quantity in tourism and hospitality industry in Vietnam, which have a large impact on customer satisfactions. There is a lack of proper training in most of the training programs in Vietnamese institutions, which cannot be recognized internationally. There is a real need for better training programs in schools and universities so that skilled workers are able to provide high quality services for both domestic and international customers. This paper analyzes the negative impacts of the lack of training on service quality, the current situations of human resource in Vietnam, and presents some weaknesses and recommendations for human resource training in Vietnam.